Majority Rule and Individual Rights: Can Rousseau’s General Will Foster Genuine Democracy in Nigeria? - Murana, Asimiyu Olalekan; Ojelade, Shola Emmanuel (Acta Universitatis Danubius. Administratio, 2025)
This study examines the tension between majority rule and individual rights in Nigeria’s democratic experience, drawing on Jean-Jacques Rousseau’s concept of the “General Will.” While democracy is premised on majority decision-making, unchecked majoritarianism in Nigeria has often led to electoral manipulation, ethnic exclusion, and the erosion of civil liberties. Using a systematic literature review and critical case analysis, including the 2007 elections and the #EndSARS protests, the study interrogates whether Rousseau’s General Will offers a viable framework for balancing collective governance with rights protection in a deeply divided society. It explores three interrelated questions: the extent to which majority rule undermines individual rights, the applicability of the General Will in Nigeria’s plural polity, and the structural reforms needed to safeguard inclusivity. Findings suggest that without institutional independence, constitutional pluralism, and enhanced civic participation, the General Will risks being appropriated by elites; however, with reforms, it could guide Nigeria toward a more genuine democracy.